Chronic Trichuris trichiura Infection Presenting as Ileocecal Valve Swelling Mimicking Malignancy. (31st October 2010) - Tuan Sharif, Sharifah Emilia; Ewe Seng, Ch'ng; Mustaffa, Nazri; Mohd Shah, Nurul Azira; Mohamed, Zeehaida
Abstract : A 46-year-old man presented with a history of passing bright red blood per rectum over the last one month. He also had on and off diarrhea with visible mucus in the stool for two months' duration. Further history was unremarkable, and physical examination revealed hemorrhoids which were subsequently banded. A colonoscopy was arranged in view of the prolonged diarrhea whereby an edematous and swollen ileocecal valve was seen. This was shown to be due to Trichuris trichiura infection, confirmed on histopathological examination of biopsies taken from the site. The patient was started on oral albendazole treatment and has been asymptomatic on latest followup. This case illustrates an accidental finding of T. trichuria infection on colonoscopic examination, which was done to investigate the patient's prolonged diarrhea.